A social cognitive approach to disaster preparedness - Calleja, Mendiola Teng (Philippine Journal of Psychology, 2015)
Using the social cognitive perspective, the study sought to determine the individual and environmental factors that predict disaster preparedness. Specifically, the research determined the relationships between risk perception, disaster experience, community disaster preparedness, and disaster preparedness behaviors. Data were collected from 401 participants from areas affected by recent typhoons and heavy monsoon rains: Tacloban and Metro Manila. Risk perception, severity of disaster experience, and community disaster preparedness were found to significantly predict the participants’ disaster preparedness behaviors. Severity of previous disaster experience seems to be the strongest determinant of individual disaster preparedness. Implications to future research and development and improvement of disaster preparations programs are discussed.